Knowledge of the Disease, Perceived Social Support, and Cognitive Appraisals in Women with Urinary Incontinence. (21st December 2016) - Szymona-Pałkowska, Katarzyna; Janowski, Konrad; Pedrycz, Agnieszka; Mucha, Dariusz; Ambroży, Tadeusz; Siermontowski, Piotr; Adamczuk, Jolanta; Sapalska, Marta; Mucha, Dawid; Kraczkowski, Janusz
Abstract : Social support and knowledge of the disease have been shown to facilitate adaptation to a chronic disease. However, the adaptation process is not fully understood. We hypothesized that these factors can contribute to better adaptation to the disease through their impact on disease-related cognitive appraisal. To analyze the links between social support and the knowledge of the disease, on one hand, and disease-related appraisals, on the other hand, one hundred fifty-eight women with stress UI, aged 32 to 79, took part in the study. Questionnaire measures of knowledge of UI, social support, and disease-related appraisals were used in the study. The level of knowledge correlated significantly negatively with the appraisal of the disease as Harm. The global level of social support correlated significantly positively with three disease-related appraisals: Profit, Challenge, and Value. Four subgroups of patients with different constellations of social support and knowledge of the disease were identified in cluster analysis and were demonstrated to differ significantly on four disease-related appraisals: Profit, Challenge, Harm, and Value. Different cognitive appraisals of UI may be specifically related to social support and knowledge of the disease, with social support affective positive disease-related appraisals, and the knowledge affecting the appraisal of Harm.